Epilepsy in patients with MOG antibody disease - Varvara E. Avdeeva; Aleksey S. Kotov (Анналы клинической и экспериментальной неврологии, 2021)
Introduction. MOG (anti-myelin oligodendrocyte glycoprotein) antibody disease is a group of demyelinating disorders of the central nervous system, in which antibodies attack the glycoproteins on the oligodendrocyte myelin membrane. The aim of the study was to evaluate the course of the disease in patients with MOG antibody disease with epilepsy.